Study of Row Hammer attack - Wenwei WANG; Peishun LIU (网络与信息安全学报)
The related technologies and defense methods of the current Row Hammer vulnerabilities were analyzed and summarized,and the security problems and possible precautions were pointed out.At the end,the current research work both at home and abroad is summarized.Two valuable directions for security research in the future are pointed out:Row Hammer exploit techniques and precautions in the ARM architecture,and accurate and controlled attacks on Row Hammer vulnerabilities.